Sustainability and luxury fashion: Generation Z´s perspective - Rosado-Pinto, F.; Jordão, C. (Global Fashion Management Conference, Proceedings, 2024)
The luxury fashion market has been growing globally since 2020 and revenues are estimated to increase at a CAGR- compound annual growth rate- of 3,8% from 2018 to 2028 (Statista, 2023). Generation Y and Z have been increasingly buying luxury goods and care the most about sustainable luxury fashion (Mohr et al., 2022; Pencarelli et al., 2020; Ranfagni & Ozuem, 2022). However, there are different points of view around the concept of sustainable luxury and authors have been studying their compatibility/ incompatibility (Pencarelli et al., 2020; Ranfagni & Ozuem, 2022). The goal of this study is to shed light on sustainable luxury fashion by examining the Generation Z´s perception of sustainable luxury and behavior towards luxury fashion. Additionally, implications for theory and for practice on how to improve the interplay between sustainability and luxury fashion for Generation Z, leveraging on technology, are also provided.